Dye-sensitized black phosphorus nanosheets decorated with Pt cocatalyst for highly efficient photocatalytic hydrogen evolution under visible light. (13th August 2019) - Xue, Yuan; Min, Shixiong; Wang, Fang
Abstract: Although black phosphorous (BP) and its derived materials have shown great potential for application in photocatalytic H2 evolution reaction (HER), their HER activity and stability still remains unsatisfied mainly due to the insufficient charge separation, the lack of surface active sites, and the defect-riched nature of BP. Herein, we report that BP nanosheets decorated with in situ grown Pt (BP NSs/Pt) could act as a highly efficient catalyst for photocatalytic H2 evolution in an Erythrosin B (ErB)-sensitized system under visible light irradiation (≥450 nm) in the presence of triethanolamine (TEOA) as sacrificial electron donor. It is found that BP NSs can provide large surface area for the confined growth of Pt nanoparticles with a high dispersion and a reduced size but also stabilize the loaded Pt nanoparticles by covalent bonds at the BP NSs/Pt interfaces. Moreover, BP NSs offer a fast electron transfer pathway to facilitate the photocatalytic HER over in situ grown Pt catalyst. As a result, BP NSs/Pt catalyst exhibits ∼6 times higher H2 evolution activity than free Pt nanoparticles and an apparent quantum yield (AQY) of 0.57% at 500 nm irradiation in ErB-TEOA system. This work indicates the potential of BP NSs as an effective 2D matrix to construct numerous high performance photocatalysts and photocatalytic systems. Highlights: Pt cocatalyst was grown in situ on BP nanosheets (BP NSs/Pt) in a ErB-sensitized photocatalytic system. ErB-sensitized BP NSs/Pt exhibits ∼6 times higher H2 evolution activity than free Pt by visible light. BP NSs provide large surface areas for highly dispersing in situ grown Pt cocatalyst with abundant exposed active sites. BP NSs offer a rapid electron transfer pathway from excited dye to loaded Pt cocatalyst.